Comparative Study for Effectiveness of Cryostretching and Static Stretching on Hamstring Flexibity in Young Females - Salma Naz, Saima Riaz, Muhammad Atif Javed, Rehan Ramzan Khan, Hafiza Neelam Muneeb, Muhammad Sulman, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the effectiveness of cryostretching and static stretching on hamstring flexibility in young females. Methodology: A quasi experimental trial was done, using non probability convenience sampling technique. Thirty young female students from Clinic of Riphah international university having hamstring tightness with at least 10 degree deficiency from 180 degree of Active Knee Extension (AKE) test upon goniometry reading were recruited. Participants were randomly allocated by lottery method into treatment and control group. The leg that showed more tightness considered as treatment leg in both groups. After 5 minutes warm up, pretreatment reading of both groups were noted. Then treatment group received cryostretching technique and control group received static stretching technique as a treatment. After treatment reading was recorded by using AKE Test as a data collection tool and results were analyzed on SPSS 17 version. Results: The mean age, BMI, Right leg and left leg circumference of treatment group is given respectively 24.00±3.40, 24.42±5.20, 49.06 ±7.05 and 49.06±6.80. Both groups showed improvement in hamstring flexibility, but treatment group show greater increase in flexibility (p=0.00). Conclusion: It was concluded from result of this study that both cryostretching and static stretching showed increase in the flexibility of hamstring muscle but cryostretching showed greater increase in flexibility of hamstring muscle.